2018
DOI: 10.1177/1098612x18783839
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent episodes of feline lower urinary tract disease with different causes: possible clinical implications

Abstract: Case series summary While descriptions of cats with recurrent episodes of feline idiopathic cystitis (FIC) exist, little is published on cats with recurrent episodes of feline lower urinary tract disease (FLUTD) where the cat is diagnosed with different causes of FLUTD at separate episodes. In the present paper, six cats, originally part of larger studies of FLUTD among Norwegian cats, are described. In the project period (2003-2009), these cats had several episodes of FLUTD. At each episode, the cats had a co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0
8

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(34 citation statements)
references
References 35 publications
1
25
0
8
Order By: Relevance
“…However, in this study, male cats showed higher UTI cases than females. UTIs can also occur in healthy male cats that are catheterized, with the risk of infection increases with the duration of catheterization [ 13 , 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, in this study, male cats showed higher UTI cases than females. UTIs can also occur in healthy male cats that are catheterized, with the risk of infection increases with the duration of catheterization [ 13 , 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…A recently published case series describes six cats with FLUTD with recurrent episodes due to different causes. 38 These cats were prospectively included in a bigger study on FLUTD and very thoroughly evaluated during every episode. Therefore, the likelihood that uroliths were missed was lower in that study and the authors discussed potential inter-related disease mechanisms between the different aetiologies.…”
Section: Figurementioning
confidence: 99%
“…The affection was more observed in males compared to females. Some researchers showed that males cats would be more susceptible to present lithiasis than females [23,26]. The narrow and long urethra of male cats makes them more likely than female cats to develop obstruction [19,27].…”
Section: Discussionmentioning
confidence: 99%
“…Several authors report that the proportion of urolithiasis is higher in cats consuming only dry food [27,30]. Food is a leading factor in the onset of urinary stones in the cat: Diet content influences urinary pH, which may increase the risk of lithiasis formation [1,4,26]. According to Bartges et a l. [31], food was essential in the prevention of urinary lithiasis.…”
Section: Discussionmentioning
confidence: 99%